2014
DOI: 10.1016/j.pain.2014.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of cutaneous neuronal purinergic receptors contributes to endothelin-1-induced mechanical hypersensitivity

Abstract: Endothelin (ET-1), an endogenous peptide with a prominent role in cutaneous pain, causes mechanical hypersensitivity in the rat hind paw, partly through mechanisms involving local release of algogenic molecules in the skin. The present study investigated involvement of cutaneous ATP, which contributes to pain in numerous animal models. Pre-exposure of ND7/104 immortalized sensory neurons to ET-1 (30 nM) for 10 min increased the proportion of cells responding to ATP (2 μM) with an increase in intracellular calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
(50 reference statements)
3
12
0
Order By: Relevance
“…Despite their overlapping spheres of influence, information on potential interplay between renal P2 and ET receptors is rare. The interaction between ET-1 and P2 signaling systems has been also demonstrated in extrarenal tissues (1,4,31,35). Our current findings demonstrate that activation of medullary P2 receptors promotes ET-1-dependent natriuresis in OVX rats, similar to male rats (23).…”
Section: Discussionsupporting
confidence: 75%
“…Despite their overlapping spheres of influence, information on potential interplay between renal P2 and ET receptors is rare. The interaction between ET-1 and P2 signaling systems has been also demonstrated in extrarenal tissues (1,4,31,35). Our current findings demonstrate that activation of medullary P2 receptors promotes ET-1-dependent natriuresis in OVX rats, similar to male rats (23).…”
Section: Discussionsupporting
confidence: 75%
“…P2X4 receptors and related purinergic mechanisms involved in T cell migration may be promising therapeutic targets in lung transplantation, as suggested by previous work showing that P2X receptor antagonists could dramatically improve long-term graft survival in a mouse lung transplant model (52). Future studies will be needed to evaluate the pharmacokinetics of 5-BDBD, to refine currently used drug regimens (53,54), and to study the efficacy of this and future P2X4 receptor antagonists in the prevention of chronic lung allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nonrenal studies demonstrated that purinergic and ET-1 signaling interact in sensory neurons (5), blood vessels (1, 13), as well as myocardium (10). Barr et al (5) provided evidence that mechanical hypersensitivity caused by cutaneous ET-1 involves sensitization of P2X 4 receptors. In porcine pancreatic arteries, P2Y 14 receptor plays vasocontractile role that involves the release of ET-1 (1).…”
Section: Discussionmentioning
confidence: 99%